2017
DOI: 10.1002/pbc.26501
|View full text |Cite
|
Sign up to set email alerts
|

Traditional and complementary medicine used with curative intent in childhood cancer: A systematic review

Abstract: Traditional and complementary medicine (T&CM) strategies are widely utilized in pediatric oncology, with many families reporting T&CM use with the intention to cure cancer. Study of T&CM agents presents many challenges, as a heterogeneous group of agents and techniques are used for a variety of different purpose in many different oncologic conditions. We present a systematic review of the literature examining published reports in which T&CM agents are used with an intention of cure. Twenty-two reports were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Plants constitute a common alternative for cancer treatment in many countries, and more than 3000 plants worldwide have been reported to have anticancer properties [ 6 , 7 ]. Although a recent study suggests that nowadays, the traditional medicines are less used, even in populous middle-income countries [ 8 ], herbal medicine use is still common in oncology therapy worldwide [ 6 , 7 , 9 , 10 , 11 ]. In the last two decades, the use of herbal remedies has also been widely embraced in many developed countries as complementary and alternative medicine, but following tight legislation and under surveillance [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants constitute a common alternative for cancer treatment in many countries, and more than 3000 plants worldwide have been reported to have anticancer properties [ 6 , 7 ]. Although a recent study suggests that nowadays, the traditional medicines are less used, even in populous middle-income countries [ 8 ], herbal medicine use is still common in oncology therapy worldwide [ 6 , 7 , 9 , 10 , 11 ]. In the last two decades, the use of herbal remedies has also been widely embraced in many developed countries as complementary and alternative medicine, but following tight legislation and under surveillance [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While just one participant felt MM could supplant chemotherapy, a recurrent theme was the possible synergistic effect of MM with conventional therapy. Two systematic reviews on use of complementary therapies in pediatric oncology indicate substantial receptivity of patients and families to using herbal remedies like MM with curative intent 24,25 . The supposition that MM has anticancer effects, sans human evidence to demonstrate this, has potential repercussions for practice 4,26 .…”
Section: Discussionmentioning
confidence: 99%
“…A national study of adults with cancer found that patients who sought complementary therapies were more likely to decline additional conventional cancer treatment and had a higher risk of mortality 27 . Although similar studies have not been conducted in children, families contending with childhood cancer may be particularly vulnerable to misinformation about the promise of understudied therapies 25,28 . Future research should seek to establish whether MM or its components have antineoplastic benefit in humans, and what its interactions might be when used concurrently with conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from therapy some Indian and African communities, traditional medicines are thought to help clean out negative spiritual influences [39] and supporters of TM/CAM use them frequently as they are generally safe at common doses [40]. More than 3000 plants based secondary metabolite worldwide have been clinically reported to have anticancer properties [41] [42]. TM/CAM medicine use is still common in oncology therapy worldwide [43] [44].…”
Section: Traditional Medicinementioning
confidence: 99%